Fully-automated in-syringe dispersive liquid-liquid microextraction for the determination of caffeine in coffee beverages. (1st December 2016) - Frizzarin, Rejane M.; Maya, Fernando; Estela, José M.; Cerdà, Víctor
Highlights: Automated dispersive liquid-liquid microextraction. In-syringe stirring for enhanced extraction. Determination of caffeine in coffee beverages. Fast and simple procedure for automated analysis in beverages. Abstract: A novel fully-automated magnetic stirring-assisted lab-in-syringe analytical procedure has been developed for the fast and efficient dispersive liquid-liquid microextraction (DLLME) of caffeine in coffee beverages. The procedure is based on the microextraction of caffeine with a minute amount of dichloromethane, isolating caffeine from the sample matrix with no further sample pretreatment. Selection of the relevant extraction parameters such as the dispersive solvent, proportion of aqueous/organic phase, pH and flow rates have been carefully evaluated. Caffeine quantification was linear from 2 to 75 mg L −1, with detection and quantification limits of 0.46 mg L −1 and 1.54 mg L −1, respectively. A coefficient of variation (n = 8; 5 mg L −1 ) of a 2.1% and a sampling rate of 16 h −1, were obtained. The procedure was satisfactorily applied to the determination of caffeine in brewed, instant and decaf coffee samples, being the results for the sample analysis validated using high-performance liquid chromatography.